Global Science Journalism Report 2021 Working conditions and practices, professional ethos and future expectations - Massarani, Luisa; Neves, Luiz Felipe Fernandes; Entradas, Marta; Bauer, Martin (CABI, 2021)
This report investigates the working conditions and climate of opinion among science journalists around the world and is part of the activities for commemorating the 20th anniversary of SciDev.Net - the Science and Development Network, which is committed to putting science at the heart of global development. In this survey, the aim is to examine science journalism around the world, considering the background, workload and work ethos of science journalists. The survey was carried out during the COVID-19 pandemic and, as such, they have also included questions investigating journalists' perceptions regarding whether (and how) the pandemic has affected them. The data were collected online between February and May 2021, from professionals working in 77 countries in six world regions: Asia/Pacific, Europe/Russia, Latin America, Northern Africa and Middle East, Sub-Saharan and Southern Africa, and the USA and Canada.